Short Circuit Effects on HV Feeders of Optimally Located Electric Vehicle Fast Charging Stations - AKAR, ONUR (My University, 2024)
Today, there is a need to expand the network of fast charging stations to encourage the use of Electric Vehicles (EV). Fast charging stations are considered mobile loads, unlike conventional electric loads. This situation brings problems in electrical distribution systems. In addition, there will be problems caused by short circuits that occur for any reason in the networks to which EVs are connected. Considering the concerns about what these problems may be and how they may be reflected in the network, it is inevitable to examine the optimal positioning of the EV on the distribution network and its possible short-circuit effects. In this study, in the Istanbul/Vanikoy pilot region, HV/LV distribution feeders and substations in the region were selected using the distribution company infrastructure. An algorithm was created using multiple location data to determine the optimal locations of one-phase and three-phase Electric Vehicle Fast Charging Stations (EVFCS) on the distribution network. Simulation of short circuit types of the system was carried out using real-time technical data such as location data of distribution transformers, power data, load density, number and length of feeders, system protection, and control element data, based on optimal locations. The effects of short circuit types on the electricity distribution network, depending on the load density of residences, other structures, and optimally located urban EVFCS, connected to the distribution transformer feeders, were analyzed.
Keywords: Bilgisayar Bilimleri; Mühendislik ve Teknoloji; Computer Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Bilgisayar Bilimi; Mühendislik; Malzeme Bilimi; Engineering, Computing & Technology (ENG); COMPUTER SCIENCE; ENGINEERING; MATERIALS SCIENCE; Genel Bilgisayar Bilimi; Fizik Bilimleri; Genel Malzeme Bilimi; Genel Mühendislik; General Computer Science; Physical Sciences; General Materials Science; General Engineering; Circuit faults; Distribution network; Distribution networks; Electric vehicle charging; EV; EVFCS; Integrated circuit modeling; Numerical models; Optimal positioning; Protection; Short circuit; Transformers